Hagen Bræ: A Surging Glacier in North Greenland—35 Years of Observations. Issue 6 (13th March 2020) - Solgaard, A. M.; Simonsen, S. B.; Grinsted, A.; Mottram, R.; Karlsson, N. B.; Hansen, K.; Kusk, A.; Sørensen, L. S.
Abstract: We use remotely sensed ice velocities in combination with observations of surface elevation and glacier area change to investigate the dynamics of Hagen Bræ, North Greenland in high detail over the last 35 years. From our data, we can establish for the first time that Hagen Bræ is a surge‐type glacier with characteristics of both Alaskan‐ and Svalbard‐type surging glaciers. We argue that the observed surge was preconditioned by the glacier geometry and triggered by englacially stored meltwater. At present, the glacier is in a transitional state between active and quiescence phases and is not building up to its pre‐surge geometry. We suggest that the glacier is adjusting to the loss of its floating section, general thinning, and changes in fjord conditions that occurred over the study period which are unrelated to the surge behavior. The high temporal resolution of the ice velocity data gives insight to the sub‐annual glacier flow. Key Points: Thirty‐five years of remotely sensed data document the recent dynamics and surge cycle of Hagen Bræ in high detail We argue that the surge was preconditioned by geometry but triggered by englacially stored meltwater The onset of the observed surge was abrupt while its termination was gradual